Does hormone replacement therapy (HRT) cause breast cancer? An application of causal principles to three studies. Issue 2 (14th March 2013) - Shapiro, Samuel; Farmer, Richard D T; Stevenson, John C; Burger, Henry G; Mueck, Alfred O; Gompel, Anne
Abstract : Background: Based principally on findings in three studies, the Collaborative Reanalysis (CR), the Women's Health Initiative (WHI), and the Million Women Study, it is claimed that hormone replacement therapy (HRT) is an established cause of breast cancer. The authors have previously reviewed those studies (Parts 1–4). The WHI findings were first published in 2002, following which the use of HRT rapidly declined. A correspondingly rapid decline in the incidence of breast cancer has been reported, and attributed to the drop in the use of HRT. The evidence, however, is conflicting. Methods: Using generally accepted causal criteria, in this article (Part 5) the authors evaluate reported trends in the incidence of breast cancer. Results: The evidence to suggest a correlated decline in the incidence of breast cancer following a decline in the use of HRT has not adequately satisfied the criteria of time order, detection bias, confounding, statistical stability and strength of association, internal consistency, and external consistency; biological plausibility is difficult to assess. Conclusions: Based on the observed trends in the incidence of breast cancer following the decline in HRT use, the ecological evidence is too limited either to support or refute the possibility that HRT causes breast cancer.